PENGARUH KARAKTERISTIK OBJEK WISATA TERHADAP KEPUTUSAN BERKUNJUNG PARA PENGUNJUNG KLENTENG SAM POO KONG DENGAN PROFIL PENGUNJUNG SEBAGAI VARIABEL MODERASI - Muhammad Afian Hartono; Nawazirul Lubis; Ngatno Ngatno (Jurnal Ilmu Administrasi Bisnis, 2016)
The development of tourism is increasing and cause changes in the behavior of visitors in tourist activities. Visitors today is not only traveled because of the desire but traveled out of necessity. This study specifically addresses the visitors at Sam Poo Kong temple.This study aims to determine the effect of the Decision Characteristics Attractions Been visitors Sam Poo Kong temple with Visitor Profile as a moderating variable. Type of explanatory research, data collection techniques are interviews with the tool questionnaire, sampling technique accidental sampling and purposive sampling with a sample size of 100. The data were analyzed through crosstab, the correlation coefficient, determination coefficient, simple linear regression, regression moderation, and t test. The data were analyzed quantitatively using the tool SPSS and qualitative.The results showed that the decision to visit categorization is quite high. Then the characteristics of the attractions categorization is high enough, the characteristics of attraction has a high influence on the decision to visit (46.8 percent) as well as the significant and positive impact on the decision to visit (0.574). The visitor profile is a potential moderating variable by variable regression coefficient of Education Decree Been insignificant and the regression coefficients to the Decision Interact Been insignificant.In conclusion the characteristics of the higher attractions, the higher the decision to visit and visitor profile has the potential to be a moderating variable. Sam Poo Kong temple suggested further improve service, regular attractions, the diversity of attractions, as well as speed of response personnel in responding to problems that occur. Besides Sam Poo Kong temple does not need to consider the profile of visitors in making policy decisions about improving the visit but should focus more on improving the characteristics of attraction.